Coping Strategy, Religiosity, and Chronic Elderly’s Life Satisfaction - Syelia Methasari; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Decrease in physical or biological conditions that occur in the elderly will result in disruption of various organs of the body so that it can cause chronic disease in the elderly. Chronic diseases can have an impact on increasing stress and life satisfaction in the elderly. This study aims to analyze the effect of coping strategies and religiosity on the life satisfaction of elderly men and women with chronic disease. The design used in this study is a cross sectional study at Medika Dramaga Hospital, Bogor Regency. Examples in the study amounted to 60 people who had chronic diseases, had suffered for more than six months and were selected by accidental sampling technique. The results showed no difference between coping strategies, religiosity, and life satisfaction of elderly men and women with chronic disease. The duration of an elderly person suffering from a disease is positively related to coping strategies. Religiosity and the duration of the elderly suffer from diseases are significantly positively related to life satisfaction. Elderly people who are still working in old age will reduce their life satisfaction. The longer the elderly suffer from chronic diseases and the higher the religiosity of the elderly, the life satisfaction of the elderly will increase.